Morality and Politics Relation: Dirty Hands Action and Posibility of Karl Popper Minimalist Democracy - Idris, Fahmi; Komariah, Aan (International Journal of Psychosocial Rehabilitation, 2020)
This research studied the problematic and political relationship of morality in political philosophy reviewed from the dirty hands and minimalist democracy possibility of Karl Popper. The method used in this research is library research with interpretative analysis. The object of research materials on the morality and political relations, which are associated with the dirty hands action and minimalist democracy possibility of Karl Popper. The formal object of this research is political philosophy. The exploration of literature studies and the analysis of moral and political relations was examined through the works of Plato, Aristotle, and Machiavelli. It was discovered that the fragmentation of unsolved moral values became central to understanding the relationship between morality and politics. Morality and politics are two things related to each other. This analysis of moral and political relations is complemented by raising the morale of the dirty hands concept that defies politicians who are increasingly symptomatic.